Zikir Abdurrauf Al-Singkili: Analysis of Islamic Psychotherapy Studies in the Treatment of Mental Disorders - Arroisi, Jarman; Saputra, Abditya Nugroho (UIR Press, 2025)
This paper examines the model of zikr taught by Sheikh Abdurrauf al-Singkili and its relevance as an Islamic psychotherapeutic approach to mental disorders. Through his works and the practices of the Syattariyah order, Abdurrauf al-Singkili emphasizes dhikr as a means of purifying the heart (tazkiyat al-nafs), cultivating moral character, and strengthening the soul through total surrender to Allah. Through qualitative research using documentary techniques, the researcher seeks to examine and explore the concept of dhikr from one of Indonesia's leading scholars of the 17th century, Sheikh Abdurrauf al-Singkili, who hailed from Aceh. The findings of this study indicate that Abdurrauf al-Singkili's dhikr, as an Islamic psychotherapy model based on the teachings of the Qur'an, can be used as a form of mental healing therapy. This can be understood from several aspects: first, Abdurrauf al-Singkili's zikir model is closely related to the spiritual dimension, which restores the balance of one's soul. second, It uses the tahlil formula in its practice, which theoretically involves deep faith in God, bringing inner peace to its practitioners. Third, The zikir model is highly practical and relevant for application, particularly in terms of breath control, which influences mental relaxation. Fourth, The zikir model relies on a spiritual guide (mursyid) as a director and guide in its implementation.